2008
DOI: 10.1063/1.2957077
|View full text |Cite
|
Sign up to set email alerts
|

O 17 and N93b NMR investigation of magnetoelectric effect in Pb(Fe1/2Nb1/2)O3

Abstract: The O17 and N93b quadrupole perturbed nuclear magnetic resonance spectra of multiferroic Pb(Fe1/2Nb1/2)O3 have been measured. The results show that the ordering at TN=143 K is antiferromagnetic with spin canting and that there is another magnetic transition around 20 K. The system consists of dielectric nanodomains and superparamagnetic clusters that order at TN, producing the magnetoelectric effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 8 publications
2
21
0
Order By: Relevance
“…The magnetoelectric constants increase supralinearly with Fe concentrations, supporting the earlier conclusions of a key role for Fe spin clustering. The room-temperature orthorhombic C 2v point group symmetry inferred from earlier x-ray diffraction studies is confirmed via TEM, and the primitive unit cell size is found to be the basic perovskite Z ¼ 1 structure of BaTiO 3 , also the sequence of phase transitions with increasing temperature from rhombohedral to orthorhombic to tetragonal to cubic mimics barium titanate. It has been known for several years [1][2][3][4][5][6] that the perovskite oxides PbFe 1/2 Ta 1/2 O 3 (PFT), PbFe 1/2 Nb 1/2 O 3 (PFN), and PbFe 2/3 W 1/3 O 3 (PFW) are multiferroics with long-range magnetic ordering near or above room temperature.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…The magnetoelectric constants increase supralinearly with Fe concentrations, supporting the earlier conclusions of a key role for Fe spin clustering. The room-temperature orthorhombic C 2v point group symmetry inferred from earlier x-ray diffraction studies is confirmed via TEM, and the primitive unit cell size is found to be the basic perovskite Z ¼ 1 structure of BaTiO 3 , also the sequence of phase transitions with increasing temperature from rhombohedral to orthorhombic to tetragonal to cubic mimics barium titanate. It has been known for several years [1][2][3][4][5][6] that the perovskite oxides PbFe 1/2 Ta 1/2 O 3 (PFT), PbFe 1/2 Nb 1/2 O 3 (PFN), and PbFe 2/3 W 1/3 O 3 (PFW) are multiferroics with long-range magnetic ordering near or above room temperature.…”
mentioning
confidence: 54%
“…The room-temperature orthorhombic C 2v point group symmetry inferred from earlier x-ray diffraction studies is confirmed via TEM, and the primitive unit cell size is found to be the basic perovskite Z ¼ 1 structure of BaTiO 3 , also the sequence of phase transitions with increasing temperature from rhombohedral to orthorhombic to tetragonal to cubic mimics barium titanate. It has been known for several years [1][2][3][4][5][6] that the perovskite oxides PbFe 1/2 Ta 1/2 O 3 (PFT), PbFe 1/2 Nb 1/2 O 3 (PFN), and PbFe 2/3 W 1/3 O 3 (PFW) are multiferroics with long-range magnetic ordering near or above room temperature. Our earlier studies showed [7][8][9][10][11][12][13][14][15][16][17] that solid solutions of these materials with PbZr x Ti 1Àx O 3 and pure PbTiO 3 yielded single-phase ferroelectric crystals whose weak ferromagnetism persists to room temperature or above.…”
mentioning
confidence: 54%
“…24 A weak cusp at ∼150 K and history dependence below ∼20 K has been observed in measurements of the bulk magnetization. [25][26][27] Neutron diffraction measurements have observed short-range three-dimensional antiferromagnetic correlations peaked at a wave vector Q = (1/2,1/2,1/2) coexisting with a magnetic Bragg peak indicative of a long-range magnetically ordered component. The presence of two distinct line shapes for the magnetic diffraction has led to models involving two phases defined by different Fe 3+ clustering sizes.…”
Section: Introductionmentioning
confidence: 99%
“…The authors 3 have shown that magnetic ground state of PFN is a spin glass like state, that coexists with the long-range AFM order below T g ≈ 20 K in the time scale of their experiment. The SG state has also been identified from 17 O NMR as distinct anomalies in the spin-lattice and spin-spin nuclear magnetic relaxation 10 . However, the microscopic nature of the above SG state as well as essential increase of magnetic susceptibility in PFN and PFT below the Neel temperature remain unclear till now.…”
Section: In Detailsmentioning
confidence: 99%
“…3, we use both relaxation time data from the ac magnetic susceptibility and those from nuclear magnetic resonance (NMR) of 17 O isotope. It has been shown previously 10 that both spin-lattice (T 1 ) and spin-spin (T 2 ) nuclear magnetization relaxation times show distinct minimum around the SG transition temperature. In particular, the T 1 relaxation time depends on electron spin fluctuations at the nuclear Larmor frequency ω/(2π) = 51.52 MHz, while the T 2 relaxation time feels spin fluctuations at much lower frequency, defined by the spin-echo delay time 2τ s = 100 µs.…”
Section: Dynamic Magnetic Susceptibilitymentioning
confidence: 99%